2010
DOI: 10.1126/science.1191040
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships for STEM Education

Abstract: Schoolteachers and higher-education faculty can benefit one another to improve teaching and student learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…Numerous reports from national policy organizations, as well as studies in the literature, have emphasized the importance of connecting the K–12 and higher-education communities to advance STEM teaching and learning (Dolan and Tanner, 2005; Tomanek, 2005; Foster et al , 2010). Bruce Alberts, former president of the National Academy of Sciences, stated that “Scientists and engineers working in partnership with local teachers represent an essential new force that will be required for effective science education reform” (Alberts, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports from national policy organizations, as well as studies in the literature, have emphasized the importance of connecting the K–12 and higher-education communities to advance STEM teaching and learning (Dolan and Tanner, 2005; Tomanek, 2005; Foster et al , 2010). Bruce Alberts, former president of the National Academy of Sciences, stated that “Scientists and engineers working in partnership with local teachers represent an essential new force that will be required for effective science education reform” (Alberts, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Students need to develop scientific and technical skills to be competitive in the twenty-first century workplace that integrates more technology than ever before (Foster et al, 2010). More specifically, undergraduate students need an education that helps them understand the scientific research process and a general knowledge of science so they can process the world around them and explain it to others.…”
Section: Background and Contextmentioning
confidence: 99%
“…Previous research [6], [7] has identified predictors for participation in informal science programs that include: previous participation, belief that it is important to do outreach, whether scientists feel capable of participating, and how much they perceive their colleagues are participating in outreach activities. On the other hand, some factors that did not predict participation were: career recognition, sustainability for their own research (even though scientists believe outreach is important, they still do not intend to participate themselves), what others think, and time and money constraints [6], [8].…”
Section: Background and Frameworkmentioning
confidence: 99%